Fuel characteristics of selected plant species regrow on burn area in Raja Musa Forest Reserve, Selangor, Malaysia - Ulok, Gerald (2015)
Tropical peat swamp forest is an important ecosystem that functions to restore balance in the hydrological process, habitat for flora and fauna as well as cater the needs for human livelihood. The forest however is threatened by many factors which lead to forest fire. There are many studies conducted to understand better the ecological balance, economic benefits, and impact of peat degradation of the forest but little is known on the species flammability which eventually provides information for forest fire risk management in tropical peat swamp forest. The aim of the study was to estimate the flammability index (FI) o the dominant plant species that were found in burnt area in Raja Musa Forest Reserve based on the its characteristics and flammability of species. The study site was located in Raja Musa Forest Reserve, Selangor, Malaysia where the forest suffered severe wildfire few years back and currently progressively rehabilitated. The fuel characteristics analyzed were moisture content, calorific value, chemical composition and thermal stability. 8 species were commonly found in the study plot and they were pioneer species of the burned area which were Scleria sumatrensis, Imperata cylindrica, Melicope latifolia, Melastoma malabathricum, Macaranga pruinosa, Lyodium flexuosum, Nephrolepis biserrata, and Uncaria tomentosa. The result shows that I.cylindica has highest ranking rate of spread and ash content. S.sumatrensis is high in coverage percentage and cellulose content while L.flexuosum is identified as goof fuel for combustion due to its low moisture content, ignition time and ignition temperature. U.tomentosa had the highest calorific value and extractive percentage amongst the analyzed species. The study found that the species flammability varies differently on its fuel characteristics basis. The flammability index exhibits that S.sumatrensis and L.flexuosum were indicated to be highly flammable and serve as good for combustion. The findings of this study provide insights of identifying the species which were highly combustible and resists fire. The fuel characteristics and flammability information were essential to recognize the significant fire threats from the species present in the area aside from peat, climatic and human causes. The evaluation, however, do not portrayed the whole Raja Musa Forest Reserve but only the affected burnt area.